Fundamental investigations into the free‐radical copolymerization of N‐phenylmaleimide and norbornene. Issue 7 (22nd October 2015) - Gmernicki, Kevin R.; Cameron, Matthew; Long, Brian K.
ABSTRACT: A fundamental investigation into the copolymerization of N ‐phenylmaleimide and norbornene via conventional free‐radical polymerization techniques was conducted. Reaction conditions were optimized for molecular weight and percent yield by tuning overall concentration and initiator loading. The copolymerization kinetics were monitored using in‐situ, variable temperature nuclear magnetic resonance and first‐order behavior was observed with respect to each monomer. Although the related copolymerization of norbornene and maleic anhydride was well‐known to proceed in a perfectly alternating manner, the copolymerization of norbornene and N ‐phenylmaleimide was found to deviate from strictly alternating copolymerization behavior, producing significant amounts of sequentially enchained N ‐phenylmaleimide units within the polymeric backbone. This deviation from perfectly alternating behavior was confirmed by analysis of individual monomer conversion rates and by measurement of monomer reactivity ratios using the Mayo–Lewis graphical analysis method. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 985–991 Abstract : Polymers containing more than one structural unit are often found to possess many desirable traits. In this report, a fundamental investigation into the copolymerization of N ‐phenylmaleimide and norbornene is presented. The polymerization conditions are optimized and the resultant polymers are analyzed to gain mechanistic insight into their polymerization. It is shown that these copolymers deviate from strictly alternating copolymerization behavior.